Color analysis and UV-VIS-NIR spectroscopy in the selection of Passiflora edulis hybrids for fresh consumption - Mateus Araújo dos Santos; Lucas Kennedy Silva Lima; Idalia Souza dos Santos; Raul Castro Carriello Rosa; Onildo Nunes de Jesus (Acta Scientiarum. Agronomy, 2025)
In this study, an alternative method was developed to evaluate fruit and pulp color, using the CIE-L*a*b* kernel space and near-infrared reflectance spectroscopy in predicting the chemical characteristics of Passiflora edulis fruits. Five passion fruit hybrids were evaluated, four with purple-skinned (H09-163, H09-164, H09-166, and H09-125) and one with yellow--skinned (H09-165), in addition to BGP418 (control, yellow-skinned). BGP418 stood out for most physical characters, mainly in the weight of the fruits (224.67 g) and the pulp with seeds (112.77 g). However, its pulp yield was 11% lower compared to other genotypes. Cluster analysis based on fruit skin and pulp color using CIE-L*a*b* space, revealed greater consistency of groups compared to using the conventional method with a color palette. A higher soluble solids content was recorded in fruits with light purple-skinned and light-yellow pulp. Based on the skin and pulp color, the other chemical characteristics did not differ between the groups formed. With UV-VIS-NIR spectra, it was possible to distinguish the genotypes in the 350 and 2,500 nm spectra and the separation between the purple and yellow-skinned l genotypes. However, there was no consistent grouping in relation to the skin and pulp color or relationship with the chemical characteristics of the fruits. The breeding program can utilize the information generated to continue the development of cultivars for fresh consumption.